2017
DOI: 10.1097/shk.0000000000000874
|View full text |Cite
|
Sign up to set email alerts
|

Cutaneous Burn Injury Promotes Shifts in the Bacterial Microbiome in Autologous Donor Skin

Abstract: Introduction The cutaneous microbiome maintains skin barrier function, regulates inflammation, and stimulates wound healing responses. Burn injury promotes an excessive activation of the cutaneous and systemic immune response directed against commensal and invading pathogens. Skin grafting is the primary method of reconstructing full-thickness burns, and wound infection continues to be a significant complication. Methods In this study, the cutaneous bacterial microbiome was evaluated and subsequently compare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
39
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(39 citation statements)
references
References 36 publications
0
39
0
Order By: Relevance
“…While the bulk of clinical research on the role of various microbiomes on wound healing has focused on chronic wounds, acute wounds (e.g., burns, blunt traumas, and penetrating traumas) are also of interest. One clinical study demonstrated that cutaneous burns significantly altered microbial skin profiles, and adjacent skin of burn sites exhibited a more similar skin microbiome to that of the burn margin as opposed to that unburned controls [ 53 ]. Burn wounds in these patients revealed an increased abundance of thermophile microbes such as Aeribacillus , Caldalkalibacilus , and Nesterenkonia and decreased abundance of Corynebacterium , both in the wound center and the skin margin.…”
Section: The Cutaneous Microbiome: Aberrations In Human Woundsmentioning
confidence: 99%
See 1 more Smart Citation
“…While the bulk of clinical research on the role of various microbiomes on wound healing has focused on chronic wounds, acute wounds (e.g., burns, blunt traumas, and penetrating traumas) are also of interest. One clinical study demonstrated that cutaneous burns significantly altered microbial skin profiles, and adjacent skin of burn sites exhibited a more similar skin microbiome to that of the burn margin as opposed to that unburned controls [ 53 ]. Burn wounds in these patients revealed an increased abundance of thermophile microbes such as Aeribacillus , Caldalkalibacilus , and Nesterenkonia and decreased abundance of Corynebacterium , both in the wound center and the skin margin.…”
Section: The Cutaneous Microbiome: Aberrations In Human Woundsmentioning
confidence: 99%
“…Indeed, topical antibiotics have largely aided burn wound outcomes by effectively treating Psuedomonas colonization. However, changes in the cutaneous microbiome were also associated with post burn complications, with Corynebacterium demonstrating a positive correlation with burn wound infection, and Staphylococcus and Propionibacterium demonstrating a negative correlation with post burn infection [ 53 ]. Interestingly, Liu et al also exhibited that skin dysbiosis is an expected consequence of burn injury that persists after healing [ 54 ].…”
Section: The Cutaneous Microbiome: Aberrations In Human Woundsmentioning
confidence: 99%
“…until the wound healed completely. [ 21 , 22 ] Related studies have shown that PRP can significantly repair severe burn wounds, while it is effective in the treatment of tissue infections such as bone infection. [ 23 , 24 ] Therefore, on the 1 hand, the application of PRP in severe burn wounds can repair the wound and reduce the generation of bacteria, on the other hand, it can prevent the invasion and infection of bacteria, thus reducing the occurrence of wound infection.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, changes to the microbiome after injury may also lead to susceptibility to colonisation. Changes to both the skin and intestinal microbiome have both previously been reported after burn injury, and these can increase susceptibility to infection [ 42 , 43 ]. Further work to understand what causes this susceptibility to infectious disease after burn injury will be important to facilitate the use of alternative interventions, either during the acute phase or after recovery to improve recovery and long-term health after burn injury.…”
Section: Discussionmentioning
confidence: 99%